Wisata Dendang Melayu Sebagai Salah Satu Potensi Wisata Bahari Di Kota Batam - Ulima Harma (Dialektika Publik, 2019)
The purpose of this research is to see the extent of the management of Dendang Melayu tourism as one of the potential marine tourism in the city of Batam in terms of facilities and attractions. This type of research used in this research is descriptive research with a qualitative approach. In this study qualitative data analysis is used by following the concept of Miles and Huberman with several stages, namely Data Reduction, Data Presentation and Conclusion. The results of this study show that the management of Dendang Melayu tourism has undergone many changes as one of the potential for marine tourism in the city of Batam, although there are still some shortcomings. Dendang Melayu Tourism is far more interesting than before because of the tourism of Tanjung Penarik, but there are some things that must be addressed, namely the condition of the facilities that are still complained by the community and the attraction of Dendang Melayu tourism for tourists.